Major poultry diseases and their temporal pattern detected through rapid tests at the Veterinary Laboratory, Pokhara, Nepal - Regmi, B; Dhakal, I; Shah, M.K.; Pande, K.R. (Nepalese Veterinary Journal, 2023)
Available within the full article